Edukasi Penggunaan Sfigmomanometer untuk Mengurangi Stres dan Meningkatkan Kepedulian Kesehatan Keluarga - Mei Putri Crismayanti; Rina Librianty; Yanita Trisetiyaningsih; Shyakira Putrie Al’-Rasyid; Pany Surya Aditya; Aldo Pratama; Maulana Afriansyah (Universitas Pahlawan Tuanku Tambusai, 2026)
The increasing number of stressors related to managing illnesses experienced by families. In this regard, family skills in using a sphygmomanometer are needed for early detection of hypertension. The purpose of this activity was to provide students with an understanding of blood pressure measurement. Through health education in the form of counseling, demonstrations, and hands-on practice using a sphygmomanometer, accompanied by discussions and questions and answers. The results of the activity showed an increase in family understanding of the correct way to measure blood pressure, increased confidence in self-monitoring their health, and reduced anxiety related to blood pressure levels. This education is expected to increase family awareness of health and support ongoing cardiovascular disease prevention.